Efek Konsumsi Kopi terhadap Kadar MDA (Malondialdehid) Tikus Terpapar Asap Rokok: Effect of Coffee Consumption on the Levels of MDA (Malondialdehyde) in Rats Exposed to Cigarette Smoke - Lizma Febrina; Aryanti Aryanti; Rolan Rusli; Laode Rijai (Jurnal Sains dan Kesehatan, 2023)
Coffee is the most commonly consumed beverage beside water. In addition to its benefits as a beverage that reduces drowsiness, coffee reportedly possesses a variety of biological activities, including antioxidant activity, antibacterial activity, and antidiabetic activity. To the best of our knowledge, no scientific studies have been published on the ability of coffee to reduce the increase in MDA levels in experimental animals exposed to cigarette smoke. The purpose of this research was to determine the possibility that coffee can indeed reduce MDA levels in animals exposed to cigarette smoke. The coffee used in this study was instant robusta coffee, which had the highest DPPH radical scavenging activity. MDA levels were determined using the TBARS method. Results indicated that coffee could decrease MDA levels by 11.84 percent. This data indicates that coffee can mitigate the negative effects of cigarette smoke exposure. Keywords: Robusta Coffee, Malondialdehyde, Cigarette Smoke Abstrak Kopi merupakan minuman yang paling banyak dikonsumsi setelah air putih. Selain manfaatnya sebagai minuman yang mengurangi rasa kantuk, kopi juga dilaporkan memiliki berbagai aktivitas biologis, seperti aktivitas antioksidan, aktivitas antibakteri serta aktivitas antidiabetes. Namun, sepanjang pengetahuan kami, belum ada laporan ilmiah mengenai kemampuan kopi dalam meredam peningkatan kadar MDA hewan coba yang dipaparkan asap rokok. Tujuan penelitian ini adalah untuk mengetahui kemampuan seduhan kopi dalam mengurangi kadar MDA hewan coba yang dipaparkan asap rokok. Kopi yang digunakan pada penelitian ini adalah kopi instan jenis kopi robusta yang memiliki aktivitas peredaman radikal DPPH yang paling baik. Kadar MDA diukur menggunakan metode TBARS. Didapatkan hasil bahwa seduhan kopi dapat menurunkan kadar MDA sebesar 11,84%. Data ini mengungkapkan kemampuan kopi dalam mengurangi efek negatif dari paparan asap rokok. Kata Kunci: Kopi Robusta, Malondialdehida, Asap Rokok